Evaluation of antivenoms in the neutralization of hyperalgesia and edema induced by Bothrops jararaca and Bothrops asper snake venoms - Picolo,G. (2002)
Neutralization of hyperalgesia induced by Bothrops jararaca and B. asper venoms was studied in rats using bothropic antivenom produced at Instituto Butantan (AVIB, 1 ml neutralizes 5 mg B. jararaca venom) and polyvalent antivenom produced at Instituto Clodomiro Picado (AVCP, 1 ml neutralizes 2.5 mg B. aspar venom). The intraplantar injection of B. jararaca and B. asper venoms caused hyperalgesia, which peaked 1 and 2 h after injection, respectively. Both venoms also induced edema with a similar time course. When neutralization assays involving the independent injection of venom and antivenom were performed, the hyperalgesia induced by B. jararaca venom was neutralized only when bothropic antivenom was administered iv 15 min before venom injection, whereas edema was neutralized when antivenom was injected 15 min or immediately before venom injection. On the other hand, polyvalent antivenom did not interfere with hyperalgesia or edema induced by B. asper venom, even when administered prior to envenomation. The lack of neutralization of hyperalgesia and edema induced by B. asper venom is not attributable to the absence of neutralizing antibodies in the antivenom, since neutralization was achieved in assays involving preincubation of venom and antivenom. Cross-neutralization of AVCP or AVIB against B. jararaca and B. asper venoms, respectively, was also evaluated. Only bothropic antivenom partially neutralized hyperalgesia induced by B. asper venom in preincubation experiments. The present data suggest that hyperalgesia and edema induced by Bothrops venoms are poorly neutralized by commercial antivenoms even when antibodies are administered immediately after envenomation.